FORMULATION AND EVALUATION OF ANTIFUNGAL NANOGEL FOR TOPICAL DRUG DELIVERY SYSTEM - PATIL, ANASUYA; KONTAMWAR, PRANOTI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Ciclopirox olamine has been used as antifungal agent. It is used as topical formulation because oral route causes irritation and ulceration of GIT. In this research work, antifungal nanogel formulated to reduce size of particle, improve in-vitro release and in-vivo release. Methods: Ciclopirox olamine nanogel was prepared by homogenization technique and incorporation of gelling agent to produce nanogel. Ciclopirox olamine nanogel formulated using Carbopol 940. Results: Antigungal Nanogels (F1-F6) were subjected to FT-IR analysis and showed no interaction between the drug and excipients. The best formulation (F6) elicited the high in-vitro release of 83.42 % at 8 hours; zeta-potential and particle size, obtained values were 230 nm and -27 mV correspondingly. In-vitro release kinetic models were shown that formulation-F6 follows First-order kinetics and high regression coefficient value r2 0.9866. SEM image of the best formulation-F6 depicts that no breakage of nanogel. The differential scanning calorimetry thermogram of ciclopirox olamine was found to be 140.09.7°C. The DSC thermogram of physical mixture of carbopol 940 and Euragit-S 100 was found to be 1290C and 218 0C. DSC study of nanogel (F6) showed no interaction between drug and excipients. The best formulation-F6 was subjected to in-vivo study on mice which showed better effect in treating dermatitis. Conclusion: It would be concluded that the best formulation-F6 which elicited better in-vitro drug release and enhanced dermatitis scoring. Keywords: Ciclopirox-olamine, Eudragit-S100, Glycerol, Dermatitis, Carbopol-940, Cellophane membrane.